The Role of the U5 snRNP in Genetic Disorders and Cancer - Wood, Katherine A.; Eadsforth, Megan A.; Newman, William G.; O’Keefe, Raymond T. (Frontiers in Genetics, 2021)
Pre-mRNA splicing is performed by the spliceosome, a dynamic macromolecular complex consisting of five small uridine-rich ribonucleoprotein complexes (the U1, U2, U4, U5 and U6 snRNPs) and numerous auxiliary splicing factors. A plethora of human disorders are caused by genetic variants affecting the function and/or expression of splicing factors, including the core snRNP proteins. Variants in the genes encoding proteins of the U5 snRNP cause two distinct and tissue-specific human disease phenotypes – variants in PRPF6, PRPF8 and SNRP200 are associated with retinitis pigmentosa (RP), while variants in EFTUD2 and TXNL4A cause the craniofacial disorders mandibulofacial dysostosis Guion-Almeida type (MFDGA) and Burn-McKeown syndrome (BMKS), respectively. Furthermore, recurrent somatic mutations or changes in the expression levels of a number of U5 snRNP proteins (PRPF6, PRPF8, EFTUD2, DDX23 and SNRNP40) have been associated with human cancers. How and why variants in ubiquitously expressed spliceosome proteins required for pre-mRNA splicing in all human cells result in tissue-restricted disease phenotypes is not clear. Additionally, why variants in different, yet interacting, proteins making up the same core spliceosome snRNP result in completely distinct disease outcomes – RP, craniofacial defects or cancer – is unclear. In this review, we define the roles of different U5 snRNP proteins in RP, craniofacial disorders and cancer, including how disease-associated genetic variants affect pre-mRNA splicing and the proposed disease mechanisms. We then propose potential hypotheses for how U5 snRNP variants cause tissue specificity resulting in the restricted and distinct human disorders.